The effects of playing digital games on children’s pain, fear, and anxiety levels during suturing: A randomized controlled study - Muhammet Kavlakci; Filiz Ogce; Tulay Yavan (Turkish Journal of Emergency Medicine)
OBJECTIVE: The aim was to determine the effects of digital game play on children’s pain, fear, and anxiety levels during suturing. METHODS: Data were obtained from 84 children between the ages of 8 and 17 years at the pediatric emergency department between January 16 and March 19, 2020, using the Socio-Demographic and Clinical Characteristics Form, the Wong–Baker Faces Pain Rating Scale (WBFPS), the Visual Analogue Scale (VAS), the Fear of Medical Procedures Scale (FMPS), and the State-Trait Anxiety Inventory for Children (STAI-CH). A four-block randomization system was used. The study group (n = 42) played digital games during the suturing procedure, unlike the control group (n = 42). Ethical permissions were obtained from the ethical committee, hospital, and families. RESULTS: Before the suturing procedure, there was no statistically significant difference between the groups’ mean scores. The intervention group was found to have statistically significantly lower WBFPS and VAS pain scores than the control group during the suturing procedure, and after the procedure, statistically significantly lower WBFPS, VAS, FMPS, and STAI-CH mean scores than the control group. CONCLUSIONS: The digital game-playing approach applied before and during the suture procedure was found to be effective in reducing children’s pain, fear, and anxiety levels.